The water defenders how ordinary people saved a country from corporate greed - Broad, Robin; Cavanagh, John 1955- (Boston Beacon Press, 2021)
"A narrative account of how El Salvador's water protectors successfully fought off an international corporation and won an unlikely battle against the World Bank"--
White men in suits (2002-2004) -- A new pact with the devil (2005) -- State of siege (2006-2008) -- Local terror, global extortion (2009) -- With a fat cat and Sun Tzu, the resistance goes global (2010-2015) -- Judgment day at the kangaroo court : "El Salvador always loses" (2016) -- Decision time : water for life, or water for gold? (2017) -- Epilogue: The vote heard round the world ... but who killed Marcelo? -- Acknowledgments -- Sources.
Bughaw is an imprint of Ateneo de Manila University Press
Includes bibliographical references.
Republication
Keywords: International Centre for Settlement of Investment Disputes; OceanaGold; Pacific Rim Mining Corporation; Gold mines and mining -- Environmental aspects -- El Salvador; Gold mines and mining -- Political aspects -- El Salvador; Environmentalism -- El Salvador -- History -- 21st century; Water -- Pollution -- Political aspects -- El Salvador